Physico-mechanical properties and shielding efficiency in relation to mineralogical and geochemical compositions of Um Had granitoid, Central Eastern Desert, Egypt - Rashwan, Mohammed A.; Lasheen, El Saeed R.; Abdelwahab, Wael; Azer, Mokhles K.; Zakaly, Hesham M. H.; Alarifi, Saad S.; Ene, Antoaneta; Thabet, Ismail A. (Frontiers in Earth Science, 2023)
The current work aims to manifest the physico-mechanical characteristics and shielding efficiency with reference to the mineralogical and geochemical compositions of the Neoproterozoic Um Had composite granitoid pluton in order to deduce their favorability as dimension stones. The Um Had granitoid pluton has an elliptical outline with a mean diameter of about 10 km. This pluton is a composite (ranging from white to reddish pink colour), hard, massive, and medium-to coarse-grained granitoid body. It's classified as syenogranites according to their modal and bulk chemical compositions. Geochemically, the granitoid pluton is a highly calc-alkaline, peraluminous granite, formed by low degree partial melting of tonalitic source rock in a post-collisional tectonic setting. The physico-mechanical properties of the granitoid pluton under study satisfy the requirements of dimension stone in terms of their bulk density (from 2561 to 2564 kg/m 3 ), and to some extent water absorption capacity (from 0.38 to 0.55%). However, their compressive strength values (50.4 to 113.4 MPa) do not achieve the minimum requirement for interior use and light duty exterior use. This study delves into the potential of some of our syenogranite samples (I, IIA, IIS, and 10) as gamma radiation shielding materials. We have assessed the mass attenuation coefficient (GMAC), effective atomic number (Zeff), exposure build-up factor (EBF), and energy absorption build-up factor (EABF) for each of these samples. The GMAC and Zeff calculations were performed using the Phy-X online software, across a photon energy range of 0.015 to 15 MeV. Our findings suggest an inverse relationship between photon energy and GMAC, with the highest values observed for the (I) granite sample (~18). This study provides a promising radiation shielding capacity of our samples. The insights derived from GMAC, Zeff, EBF, and EABF can serve as a guiding beacon for the development of effective, naturally sourced radiation shielding materials.